A study of creativity in the teaching and learning history towards development of active students in Lahad Datu, Sabah - Agus, Ariegusrini; Salleh, Mohamad Johdi (2011)
This study was aimed to identify creativity in the teaching and learning History towards development of active students in two selected secondary schools in Lahad Datu, Sabah. This study was based on the data collected from questionnaires and interviews in both schools which involved 189 students of various ethnicity including Bajau, Kadazan, Idahan, Chinese, Indians and Malay. The collected data then analyzed by using convenience statistics such as frequency, mean, standard deviation, and independent samples test. The results show that creativity in the teaching and learning History influenced the development of active students, however, gender and ethnics are not the main yardsticks in measuring the level of activeness in learning History subject. If the teachers have the ability in attracting their student’s attention during the learning session, there will be possibilities that the entire levels of students without counting their gender and ethnics will love to learn History. It is hoped that more students would benefit from this core subject of the lower and upper secondary levels, ICSS Malaysia, towards the realisation of the twenty-first millennium first class human capital of Malaysian in the era of globalization..